Evaluación de índices de cosecha, diámetro y períodos de endulzamiento en el Cultivo de Jícama (smallanthus sonchifolius.) en el Campus Experimental Salache, en el período 2018-2019. - Ortiz Chicaiza, Nataly Rosana (2019)
The research was developed in the Experimental Salache School, (CEASA) at Technical University of Cotopaxi in the period 2018-2019, had as objective to evaluate the indexes of harvest and to describe the behavior in harvest and postharvest of jicama considering the average diameter and periods of sweetening, The first phase of the work was carried out in field was harvested in two indexes, 270 and 288 days. For the post-harvest phase, 40 and 60 mm roots were used to be exposed to the sweetening process in three periods of time: 5, 10 and 15 days, and a witness not exposed to the sun was used. The variables evaluated in the laboratory were: color, weight, and weight variation, incidence of plagues, diseases and physio pathologies. We worked under an experimental design in a DBCA with 16 treatments and 3 repetitions. Jicama root harvested at 270 days obtained a weight of601.04 gr, a weight variation of 15.9% and a 41.67% incidence of plague, disease and physio pathologies. The diameter that reported the best results was 60 mm with a weight of 691.5 gr and a weight variation of 15.89%. The adequate period for sweetening was 10 days with a weight variation of 17% and an 86.67% incidence of plague, disease. The best treatment was T3 (270 days; 60mm; 10 days for sweetened) with a weight variation of 15.2. In order to avoid weight loss and increase the sweetness of the tuberous root, it should be exposed to 10 days for sweetening.